Alimentación del pejerrey (Basilichthys bonariensis bonariensis, Atherinidae) en laguna Chascomús (Buenos Aires, Argentina) : Relaciones ecológicas de complementación y eficiencia trófica del plancton - Ringuelet, Raúl Adolfo (1980)
This paper refers about the alimentary relations of the argentine silverside. We examined its digestive tract, and described tbe trophic spectrum of very juvenile specimens and adults. This fish is normally planktophagous, but it retains, by means of a selective filtration, mostly microcrustaceans: firstly Calanoids, secondly Cyclopids and lastly Cladocerans. The proportion of plankters in Chascomús pond is enterely different from that retained in the digestive tract of the “pejerrey”. We analysed this phenomenon and calculated the retention and loss coefficients. The wet weight of the microcrustaceans retained in 5.485 liters of water is equivalent to 1 gram fish; in other words, the relationship is 1 gram fish = 0,87 g of effective zooplankton.